A study of prescribing pattern of micronutrients in dermatology outpatient department at tertiary care teaching hospital - Shah, Anjali; Pillai, Ajita (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Skin is the first line of defence for protecting our bodies against external perturbations, including ultraviolet (UV) irradiation mechanical/chemical stress, and bacterial infection. Different vitamins and trace elements are vital for skin health. The present study was planned to define the prescription pattern of micronutrients in the different skin diseases. Methods: An observational and cross-sectional conducted in the out-patient department of dermatology at a tertiary care teaching hospital in Rajkot, Gujarat over a period of two months. Prescriptions of 200 patients were analysed. Results: In our study, 200 prescriptions were evaluated. The average number of micronutrients per prescription was 1.95. In male average number of micronutrients per prescriptions was 2.01 while in female it was 1.91. Multivitamin B complex was the most commonly prescribed micronutrient. Conclusions: We observed that multivitamin B complex was the most commonly prescribed micronutrients followed by vitamin C in skin diseases. Though micronutrients play an important role in the body for healthy skin, it is overprescribed.